2022
DOI: 10.3390/genes13101868
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of MicroRNAs and Autophagy Mechanism in Pancreatic Cancer Progression: Future Therapeutic Approaches

Abstract: Pancreatic cancer constitutes the fourth most frequent cause of death due to malignancy in the US. Despite the new therapeutic modalities, the management of pancreatic ductal adenocarcinoma (PDAC) is considered a difficult task for clinicians due to the fact that is usually diagnosed in already advanced stages and it is relatively resistant to the current chemotherapeutic agents. The molecular background analysis of pancreatic malignant tumors, which includes various epigenetic and genetic alterations, opens n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…Deep knowledge of the miRNA tumor profiles including PDAC, could lead to the development of powerful anti-cancer therapeutic tools. There are several alterations in the expression levels of miRNAs in PDAC, which can facilitate its diagnosis, and can be utilized as targets for tumor suppression via inhibiting the oncomiRs or enhancing the expression of tumor-suppressive miRNAs [ 35 ].…”
Section: An Overview Of the Implication Of Mirnas And Other Non-codin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Deep knowledge of the miRNA tumor profiles including PDAC, could lead to the development of powerful anti-cancer therapeutic tools. There are several alterations in the expression levels of miRNAs in PDAC, which can facilitate its diagnosis, and can be utilized as targets for tumor suppression via inhibiting the oncomiRs or enhancing the expression of tumor-suppressive miRNAs [ 35 ].…”
Section: An Overview Of the Implication Of Mirnas And Other Non-codin...mentioning
confidence: 99%
“…Moreover, MALAT1 induces activation of the autophagy pathway. PDAC constitutes a malignancy that presents overregulation of autophagy that needs to be suppressed, compared to other malignancies, in which autophagy inhibition could lead to oncogenesis [ 35 , 73 , 75 , 76 ]. Furthermore, AFAP1-AS1 promotes PDAC growth and invasion by upregulating the IGF1R oncogene via miR-133a sequestration, which regulates its translation [ 77 ].…”
Section: An Overview Of the Implication Of Mirnas And Other Non-codin...mentioning
confidence: 99%
“…However, recent studies have demonstrated evidence of mutual control between the autophagy pathway and the miRNA machinery. Indeed, in some other cases, degradation mediated through autophagy and autophagy can target miRNA and miRNA machinery components thus playing an important role in the control of cancer progression [61][62][63].…”
Section: Regulation Of Mirnas By Autophagymentioning
confidence: 99%
“…There is a call for the discovery and development of novel therapeutic approaches, with the understanding of the molecular complexity of this malignancy being pivotal. The role of extracellular vesicles (EVs) and non-coding RNA molecules and their implications in HCC development and progression are in the spotlight of their ongoing studies, aiming to discover novel therapeutic targets and strategies[ 3 ].…”
Section: Introductionmentioning
confidence: 99%